Fenomena Gaya Hidup Konsumtif dan Flexing di Media Sosial Facebook pada Perempuan : Studi Kasus di Desa Monggas - Raja Azura; Suud Suud; Risma Ade (Universitas Muhammadiyah Mataram, 2026)
This study aims to describe and analyze the phenomenon of consumptive lifestyles and flexing behavior on Facebook among women in Monggas Village, Central Lombok Regency. The study employed a qualitative approach using a phenomenological method. Informants were selected through purposive sampling, while data were collected through non-participant observation, in-depth interviews, and documentation. Data were analyzed using Creswell’s phenomenological analysis. The findings reveal that consumptive behavior is influenced by Facebook use, peer influence, and the desire to follow current trends. The identified forms of consumptive behavior include impulsive buying, excessive purchasing, and irrational purchasing, whereas flexing behavior is manifested through posting consumption-related activities to gain attention and social recognition. These findings highlight the importance of strengthening digital literacy and promoting responsible consumption to mitigate the negative social impacts of social media use.